HOW SUCCESSFUL PEOPLE THRIVE IN A HYPER‐CONNECTED WORLD. Issue 102 (17th September 2021) - Cross, Rob
Abstract: The author contends that with the explosion of workplace collaboration, the benefits have been accompanied by "significantly less time for focused individual work, thoughtful reflection and sound decision‐making." This leads to stress, burnout, and unhappy organizations. "Network analysis, " he says, "enables leaders to map patterns of collaboration and information flow between people within their organizations. It provides a way of both visualizing group connectivity and quantitatively profiling network dimensions that relate to individual performance and well‐being." His research reveals that part of what causes these problems can be the beliefs executives hold about collaboration and being more productive and helpful to others. These beliefs included, in the author's words: (1) Identity and reputation triggers such as too great a desire to help, sense of fulfillment from accomplishment, desire to be influential or recognized for expertise, concern about being labeled a poor performer, teammate, or leader and need to be right and (2) anxiety and need for control triggers such as fear of losing control, need for closure, discomfort with ambiguity, and FOMO/Fear of Missing Out. He concludes with a checklist for effectiveness, including more streamlined emails and efficient use of email norms, and holding structured meetings focused on desired outcomes.